Pseudo aneurysm of the uterine artery with arteriovenous fistula after cesarean section: A rare but sinister cause of delayed postpartum hemorrhage. Issue 3 (29th June 2020) - Pohlan, Julian; Hinkson, Larry; Wickmann, Ulrike; Henrich, Wolfgang; Althoff, Christian E.
Abstract: Pseudoaneurysm of the uterine artery is a rare complication of cesarean section. Delayed diagnosis and management may result in rapid and catastrophic postpartum hemorrhage and may necessitate hysterectomy or can even be fatal. A 28‐year‐old woman (gravida I, para I) presented with delayed postpartum hemorrhage 10 days after emergency cesarean section. Using transabdominal and transvaginal Color Doppler sonography, we detected a pseudoaneurysm in the posterior uterine wall, which was successfully treated with selective embolization distal and proximal to the lesion with platinum coils. In patients with delayed postpartum hemorrhage—especially after cesarean section—the rare possibility of uterine artery pseudoaneurysm must be kept in mind.